ANALISIS POTENSI CAGAR BUDAYA KOTA MAGELANG DENGAN SKORING - Arif Barata Sakti; Eny Sulistyowati (Badan Perencanaan Pembangunan Daerah Kota Magelang, 2020)
The Local Cultural Analysis Activity of the Magelang Municipality (Focus on Cultural Heritage) intends to obtain a study of the potential and problems of cultural heritage based on public opinion, analyze, and recommend measures of protection. While the purpose of this activity is to get a picture of the potential of cultural heritage in the Magelang Municipality, explore perceptions / understandings of opinions from various parties, physically and accessories of buildings / areas according to the style at the time of his style, analyze potential opportunities and threats related preservation of cultural heritage, and provide alternative cultural heritage recommendations as a reference policy and necessary steps. The method used in this research is a quantitative. The quantitative approach is carried out through scoring on ancient or historic buildings. From this study ten buildings have been identified as Cultural Heritage, namely Dapur Umum Tulung, Tugu Jam Alun-alun, Mbah Dudo's Tomb, Van der Steur's Tomb, House of dr. Setyati Pranantyo, Lumpang Mantyasih Site, Badaan Area, Poncol Area, Gunung Tidar Tombs, and Japanese Bunkers. Recommendations from this study include namely aspects of protection (rescue, security, maintenance, restoration).